Improving the Physical Properties of Iraqi Bauxite Refractory Bricks. - Al-Amer, Enass Mohy Hadi; Al-Kadhemy, Mahasin F Hadi (Al-Nahrain Journal of Science, 2018)
In this study; physical and mineralogical test were carried out on the Iraqi bauxite mineral in order to assess its suitability for the production of refractory bricks. Two types of additives were used, Iraqi white kaolin as a binding material in ratio 10%, and (micro and nano) zirconia as additives, synthetic zirconia in ratios of (5, 10, 15, 20) % for the purpose of improving the general characteristics of the Iraqi bauxite bricks. The bricks were formed by semi-dry pressing, with added potassium silicate in ratio 10% as binder material.The formed samples were of cylindrical shape (50×50) mm for diameter and height. The drying process of the samples was carried out at 110˚C for 24h, then firing at 1400˚C and soking time 2h. Physical properties such as microstructure by (SEM) and (XRD) analysis for bricks test were carried out.